Landscape Reclamation Rising From What's Left - Loures, Luis (IntechOpen, 2020)
Ongoing landscape transformation worldwide has raised global concerns and there is a need to rethink landscaping to protect the environment. This is especially true for previously developed sites, currently abandoned or underused. Instead of consuming green lands, these derelict landscapes need to be redeveloped and given new life, enabling their transition to an increasingly sustainable urban setting. In this scenario, the present book, considers a set of subjects that highlight the diverse nature of the scientific domains associated with landscape reclamation, emphasizing the need to acknowledge that the contribution of each sustainability dimension is equally important. This will offer complementary development opportunities, while enabling redeveloped landscapes to fulfill multiple functions in an integrated way and underline the relevance of multifunctionality to promote sustainable landscape reclamation, planning, and development.